Disaster Mitigation through Team Games Tournament (TGT) Model Based on Start with A Question in Learning - Khairil Khairil; Afdhal Afdhal (Jurnal Penelitian Pendidikan IPA, 2025)
Along with the increasing frequency of natural disasters, disaster mitigation education becomes crucial in geography learning. However, students at SMA Negeri 7 Seluma Bengkulu often struggle to understand disaster mitigation concepts due to a lack of interactive and engaging learning methods. This study aims to analyze the effectiveness of the Team Game Tournament (TGT) learning model in improving students' understanding of disaster mitigation. This study used an experimental approach, with class X.1 as the experimental class of 25 students and class X.3 as the control class of 25 students. The instruments used to collect data included observations to see the application of the learning model and questionnaires to measure students' understanding of disaster mitigation. Data analysis was conducted using the Anova test. The findings indicate that the Start with a Question-based Teams Games Tournament learning model significantly enhances students' understanding of disaster mitigation compared to the traditional lecture method, as evidenced by a significance value (2-tailed) of 0.001 < 0.05. This research suggests that integrating interactive learning models can improve disaster preparedness among students